Violence against housemaids in an Ethiopian town during the early phase of the COVID-19 pandemic: a cross-sectional study - Metadel Adane; Helmut Kloos; Yordanos Mezemir; Amare Muche; Erkihun Amsalu (BMC, 2023)
Abstract Background Violence against women is a global public health problem that has numerous adverse effects. However, published literature regarding violence against housemaids during the COVID-19 pandemic in Ethiopia is lacking. The current study aims to explore the experiences of violence and associated factors among housemaids in Ethiopia. The findings may be useful to the design appropriate policies, programs and strategies to reduce the problem. Methods A community-based cross-sectional study was conducted from January to March, 2021 in Kombolcha Town, Ethiopia. A total of 215 housemaids aged 14 years and older were included in the study using a simple random sampling technique. A multivariable logistic regression model with 95% CI (confidence interval) was applied to identify significant factors of physical and sexual violence. Variables with a P-value < 0.05 were declared as factors significantly associated with violence. Results Among 215 housemaids, 33.49% (95% CI: 27.13-39.85%) reported physical violence and 21.4% (95% CI: 15.87-26.92) reported sexual violence during the COVID-19 pandemic. Thus, housemaids aged 19-23 years (AOR = 2.64, 95% CI: 1.01-6.89), who had a male employer (AOR = 2.39, 95% CI: 1.05-5.45), whose employers chewed chat (Catha edulis) (AOR = 3.78, 95% CI: 1.73-8.29), or drank alcohol (AOR = 2.90, 95% CI: 1.17-7.17) experienced more physical violence. Sexual violence was also associated with employers' alcohol consumption (AOR = 9.72, 95% CI: 3.12-20.31), employers' chat chewing (AOR = 7.40, 95% CI: 2.26-14.21) and male employers (AOR = 3.23, 95% CI: 1.22-8.52). Conclusion The findings indicate that one in five housemaids and one in three housemaids experienced sexual violence and physical violence, respectively. Housemaids aged 19-23 years, having a male employer, having an employer who chewed chat (Catha edulis) or who drank alcohol were factors associated with physical violence, whereas employers' alcohol consumption, employers' chat chewing and male employers were factors associated with sexual violence.